Case Study: Teaching with Industry (TWI) Using New Videoconferencing Technology and Innovative Classroom Setups - Francois Jacobs; William Cain; Renxiang Lu; Amy Daugherty (MDPI AG, 2022)
This paper describes a case study of a novel teaching method where the "Teaching with Industry" (TWI) model-industry practitioners incorporated as co-instructors in a semester-long classroom setting-is enhanced by using new videoconferencing technologies such as Zoom and Meeting Owl Pro, and innovative classroom setups. This enhanced model was developed with the intent to bridge the gap between information acquired in the classroom and the skills and competencies required in the industry. The different teaching platforms not only facilitated the teaching when industry practitioners were/are not able to be physically present in the classroom, but also led to efficient organization of the different activities carried out in class. Results obtained from end-course surveys showed that students had a positive experience using Zoom and Meeting Owl Pro welcoming the opportunity to engage with industry practitioners and gain better understanding of the practical usefulness of the course.